The Moral Impacts of Organizational Stress on Correctional Officers - Ricciardelli, Rose (Criminal justice review, 2025)
Organizational stress (i.e., structural aspects of the organization such as excessive workload, shiftwork, gossip) has long been found by public safety personnel to be more impactful on their health and wellness than operational stress (i.e., inherent stresses of the job such as altercations, intervention in suicide behaviors). In the current study, which engages semi-structured interviews conducted with 28 correctional officers employed at one provincial prison in Atlantic Canada, we unpack through a lens of moral distress four prevalent sources of organizational stress among correctional officers that emerged in the data without categories precogitated, with a focus on participant experiences and expressed similarities across accounts: (1) management, (2) staff retention, (3) training needs, (4) lack of mental health support. Findings indicate organizational stress has a significant impact on correctional officers and these sources of organizational stress are exacerbated by officers’ moral and ethical vulnerabilities emergent from their conditions of employment. We recommend several practical changes to ease the strains and moral harms felt by correctional officers and better support their mental health and well-being, such as increasing staffing levels, providing more education and training opportunities for frontline officers and senior leaders, and providing more adequate mental health support for correctional officers.